Tarian Ka’bawakng sebagai Doa Tubuh: Inkulturasi Budaya Dayak Kanayatn dalam Liturgi Gereja Katolik - Kristina Meni; Tjang, Yanto Sandy; Amandus Suhaedi Dol; Felisitas Yuswanto (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study examines the Ka’Bawakng dance as a cultural–religious expression of the Dayak Kanayatn community that has undergone a deepening of meaning through inculturation within Catholic liturgy. Originating in the Baliatn ritual, Ka’Bawakng dance initially functioned as a medium of healing and cosmological communication that affirmed the interconnectedness of human beings, nature, and Jubata. In its encounter with the Catholic faith, the dance was incorporated into the Eucharistic celebration as an offertory dance through symbolic reinterpretation grounded in the principles of inculturation articulated by the Second Vatican Council. This research employs a hermeneutical approach using participant observation, in-depth interviews, and documentary study, analyzed through thematic analysis. The findings indicate that Ka’Bawakng dance is not treated as a merely decorative liturgical element, but is understood as a language of prayer engaging the body, cultural memory, and the spirituality of the faithful. This integration deepens liturgical participation, strengthens the religious–cultural identity of the Dayak Kanayatn community, and creates a constructive space for dialogue between ancestral traditions and Christian faith. Nevertheless, sustaining the inculturation of Ka’Bawakng dance requires ongoing pastoral accompaniment to ensure fidelity to Church liturgical norms while respecting local cultural values.